FUNCTION AND STRESS ("Conference on Universal Science Research 2023", 2024)
Stress is the emphasis of any language unit in a speech stream. In English, stress can be used to highlight a syllable, a word, or even an entire phrase. Accordingly, stress can be verbal, syntagmatic and phrasal. Word stress emphasizes a particular syllable in a word. In English transcription, such stress is indicated by a special symbol ['] placed before the stressed syllable. Syntagmatic or tact stress highlights the most important word in one speech tact (syntagma) during the pronunciation of the text. Phrase stress allows you to distinguish several words (syntagma) in a sentence at the same time. Misplaced stress changes the sound of a word, making it difficult to understand. In fluent speech, stress helps distinguish similar words.